2016
DOI: 10.1002/chem.201601406
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic (Alkyl)(Amino)Carbene Complexes of Rhodium and Nickel and Their Steric and Electronic Parameters

Abstract: N-heterocyclic carbenes (NHCs) and cyclic (alkyl)(amino)carbenes (CAACs) are of great interest, as their electronic and steric properties provide a unique class of ligands and organocatalysts. Herein, substitution reactions involving novel carbonyl complexes of rhodium and nickel were studied to provide a deeper understanding of the fundamental electronic factors characterizing CAAC(methyl) , which were compared with the large array of data available for NHC and sterically more demanding CAAC ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 100 publications
5
50
1
4
Order By: Relevance
“…This is consistent with Tolman's substituent additivity rule stating that each substituent at the P atom has an individual contribution to the overall donor strength of the phosphine . Phosphine 3 has the lowest reported TEP value among the known phosphines and is a better donor ligand than well‐established carbene ligands such as the N ‐heterocyclic carbene NHC1 (2051.5 cm −1 ), the cyclic alkylaminocarbene NHC2 (2046.1 cm −1 ) or the abnormal N ‐heterocyclic carbene NHC3 (2038.5 cm −1 ) …”
Section: Figuresupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with Tolman's substituent additivity rule stating that each substituent at the P atom has an individual contribution to the overall donor strength of the phosphine . Phosphine 3 has the lowest reported TEP value among the known phosphines and is a better donor ligand than well‐established carbene ligands such as the N ‐heterocyclic carbene NHC1 (2051.5 cm −1 ), the cyclic alkylaminocarbene NHC2 (2046.1 cm −1 ) or the abnormal N ‐heterocyclic carbene NHC3 (2038.5 cm −1 ) …”
Section: Figuresupporting
confidence: 84%
“…[a] Literature values determined from [ L Ni(CO) 3 ] . [b] Literature value determined from [ L IrCl(CO) 2 ] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Within the set of cyclic carbenes that have been investigated, it can be concluded that the p-accepting ability of CAACs is among the strongest, and is only surpassed by diamidocarbenes XVIII and XXIV.Note that, unlike the TEP values,l arge differences of 31 Pc hemical shifts are observed (Dd > 150 ppm). [56,57] Shortly after our group reported the "Pscale," Ganter et al established ar anking of the p-accepting ability of carbenes using the 77 Se NMR chemical shift of carbene-selenium adducts. [58] As imilar order of carbenes electrophilicity was obtained.…”
Section: Electronic Properties Of Caacsmentioning
confidence: 99%
“…Verglichen mit NHCs weisen cAACs einen kleineren HOMO‐LUMO‐Abstand auf und stellen somit gleichzeitig stärkere Elektrophile und stärkere Nukleophile dar . Diese Eigenschaften befähigen cAACs zur Aktivierung kleiner Moleküle, wie CO, H 2 und P 4 , sowie zur Aktivierung anderer enthalpisch starker Einfachbindungen, wie B‐H, C‐H und C‐F . Dieser elektrophilere Charakter der cAACs und ihre erhöhte Stabilität gegen eine Ringerweiterung motivierten uns dazu, diese Moleküle für Kohlenstoff‐Element‐Bindungsaktivierungen zu untersuchen .…”
Section: Figureunclassified